Biophysical analysis of cancer stem cell-potent copper(ii) coordination complexes. Issue 18 (11th January 2019) - Zheng, Puyi; Eskandari, Arvin; Lu, Chunxin; Laws, Kristine; Aldous, Leigh; Suntharalingam, Kogularamanan
Abstract : Copper(ii ) coordination complexes, 1 and2, containing nonsteroidal anti-inflammatory drugs (NSAIDs) potently kill breast cancer stem cells (CSCs) and bulk breast cancer cells. Abstract : Copper(ii ) coordination complexes, 1 and2, containing nonsteroidal anti-inflammatory drugs (NSAIDs) potently kill breast cancer stem cells (CSCs) and bulk breast cancer cells. Although detailed biological studies have been conducted to shed light on their mechanism of cytotoxicity, little is known about their molecular level mechanism of action. This biophysical study, aided by the preparation of a fluorophore-containing analogue, 3, reveals that the complexes operate by undergoing reduction to a copper(i ) form and releasing the associated NSAIDs.